Interpretation of the Period and Person in the Story "Caravan Bell" - M. Hamrayeva (Genius Publishing Group, 2022)
In this article, The Story Of The Wave Monument "caravan Bell" in Uzbek Literature, among the works dedicated to Sahibkiran Amir Temur is quite energetic in artistic terms, and the history is correct and truthful, at the same time, the wave monument was effectively created on this historical subject, wrote a number of works on the historical subject as a product of, it is also important that issues related to what principles are based on the creation of entrepreneurship are discussed.
Keywords: Historical subject; personality spirit; art of mental analysis; landscape image